New species of Ilanga (Gastropoda: Trochoidea: Solariellidae) from the Indo-West Pacific - Vilvens, Claude; Williams, Suzanne T. (Zootaxa, 2020)
In this study we list and figure a total of 22 species assigned to the genus Ilanga Herbert, 1987 that were collected during recent Paris Museum expeditions, of which 16 are new and described here (listed in the order they appear in the text): Ilanga herberti n. sp., I. euryomphalos n. sp., I. polygramma n. sp., I. stephanophora n. sp., I. harrytaylori n. sp., I. eurystoma n. sp., I. oxeia n. sp., I. cosmia n. sp., I. corrineae n. sp., I. comes n. sp., I. dongshaensis n. sp., I. philia n. sp., I. helicoides n. sp., I. lauensis n. sp., I. mesembrine n. sp. and I. boreia n. sp.. These species occur throughout the Indo-West Pacific, extending the known range of this genus beyond the south west Indian Ocean. We also synonymise Microgaza fulgens Dall, 1907 and Microgaza konos Vilvens, 2009 (syn. nov.) (as I. fulgens). New combinations include Ilanga fulgens and I. navakaensis.